Investigation of indoor radon concentration in dwellings and public places of Firuzkuh - M Banar; AR Mesdaghinia; K Naddafi; MS Hassanvand (سلامت و محیط, 2019)
Background and Objective: Radon is a radioactive, odorless gas. Radon gas with the emission of alpha radiation and sticking to aerosols in the air can cause lung cancer. This study evaluated the concentration of radon in residential houses and public places in Firuzkuh city and compared the values with the recommended international guidelines. Materials and Methods: Radon gas concentration was measured by passive measurements using CR-39 detectors. The detectors were placed in houses and schools of the city for three months. After this time, the detectors were located and placed in a 6.25% normal solution at 85 °C for 4 hours in a laboratory. After preparation, using an automatic scan and appropriate statistical method, the concentration of radon gas was determined. Results: The results indicated that the average concentrations of radon gas in homes and public places were 137.74 and 110.17 Bq/m3, respectively. Comparing the results with the WHO guideline showed that 76.3% of the homes and 66.7% of the sites had a concentration above the guideline (100 Bq/m3). Conclusion: The results of this study can be used to prepare the National Radon gas map in the country.